Effects of Communication Competency and Self-Esteem on Gaming Addiction Symptoms - Şaliş, İrem and Topçu Bulut, Merve (Addicta: The Turkish Journal on Addictions, 2022)
Gaming behavior has become more and more popular, but there has not been any research that considers the relationship between communication competency, self-esteem, and internet gaming addiction symptoms. The main aim of the ongoing study was to assess the associations between internet gaming addiction symp-toms, self-esteem, and dimensions of communication competency. For this purpose, data were obtained from 455 individuals (47.7% females and 52.3% males) who reported that they are involved in gaming. In this study, participants were assessed with the following scale set: Sociodemographic Form, Internet Gaming Disorder Scale-Short Form, Communicative Competence Scale, and Rosenberg Self-Esteem Scale. Analyses indicated that the internet gaming disorder total score has a significant and negative correlation with self- esteem and dimensions of communication competency. Besides these results, self-esteem and listening com-petency of dimensions of communication competency have been found as a significant predictor of internet gaming disorder total score. In the literature, there has been only finite published research analyzing the dimensions of communication competency, self-esteem, and internet gaming disorder.